Translating Basic Science Research to Clinical Application: Models and Strategies for Intracerebral Hemorrhage - Leonardo, Christopher C.; Robbins, Sean; Dore, Sylvain (Frontiers in Neurology, 2012)
Preclinical stroke models provide insights into mechanisms of cellular injury and potential therapeutic targets. Renewed efforts to standardize preclinical practices and adopt more rigorous approaches reflect the assumption that a better class of compounds will translate into clinical efficacy. While the need for novel therapeutics is clear, it is also critical that diagnostics be improved to allow for more rapid treatment upon hospital admission. Advances in imaging techniques have aided in the diagnosis of stroke, yet current limitations and expenses demonstrate the need for new and complementary approaches. Intracerebral hemorrhage (ICH) exhibits the highest mortality rate, displays unique pathology and requires specialized treatment strategies relative to other forms of stroke. The aggressive nature and severe consequences of ICH underscore the need for novel therapeutic approaches as well as accurate and expeditious diagnostic tools. The use of experimental models will continue to aid in addressing these important issues as the field attempts to translate basic science findings into the clinical setting. Several preclinical models of ICH have been developed and are widely used to recapitulate human pathology. Because each model has limitations, the burden lies with the investigator to clearly define the question being asked and select the model system that is most relevant to that question. It may also be necessary to optimize and refine pre-existing paradigms, or generate new paradigms, as the future success of translational research is dependent upon the ability to mimic human sequelae and assess clinically relevant outcome measures as means to evaluate therapeutic efficacy.